2019
DOI: 10.1002/kjm2.12125
|View full text |Cite
|
Sign up to set email alerts
|

The association between glycated albumin, glycohemoglobin, and glycated albumin to glycohemoglobin ratio in diabetic retinopathy of prediabetes

Abstract: Prediabetes increased risk of diabetes and diabetes-related macrovascular and microvascular complication. Glycohemoglobin (HbA 1c ) is clinically used as the gold standard for glycemic control of diabetes. Glycated albumin (GA) is an early Amadori-type glycation protein between glucose and serum albumin, which changes in a shorter period of time than HbA 1c and is superior to HbA 1c in reflecting fluctuations in blood glucose. In this study, we aim to assess the predictive value of GA and glycohemoglobin (HbA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(30 reference statements)
1
4
0
Order By: Relevance
“…Data analysis revealed that approximately 8% of participants with IGT had DR. ( Diabetes Prevention Program Research, 2007 ) The association between IGT and DR also correlated with other studies demonstrating that DR incidence rose linearly with an increase in blood glucose (especially HbA1c levels). ( Cheng et al, 2009 ; Lee et al, 2019 ) Overall, the various findings support the proposition that microvascular complications, particularly DR, involve gradual and continuous processes triggered by chronic exposure to glucose. Moreover, microvascular complications may occur before diabetes is clinically diagnosable.…”
Section: Discussionsupporting
confidence: 60%
“…Data analysis revealed that approximately 8% of participants with IGT had DR. ( Diabetes Prevention Program Research, 2007 ) The association between IGT and DR also correlated with other studies demonstrating that DR incidence rose linearly with an increase in blood glucose (especially HbA1c levels). ( Cheng et al, 2009 ; Lee et al, 2019 ) Overall, the various findings support the proposition that microvascular complications, particularly DR, involve gradual and continuous processes triggered by chronic exposure to glucose. Moreover, microvascular complications may occur before diabetes is clinically diagnosable.…”
Section: Discussionsupporting
confidence: 60%
“…Currently, fructosyllysine, glycated albumin (GA) and glycated hemoglobin (HbA1c) are used in clinical practice. However, they are not proper AGE but less stable Amadori products [ 31 , 32 , 33 ]. Therefore, longer-lived and stable AGE markers are sought after.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2019 study among patients with prediabetes (IFG + HbA1c 5.7–6.4%), DR was diagnosed in 24.1% of the group. The percentage of people with DR increased linearly together with the increasing percentage of HbA1c, respectively: HbA1c < 5.7%: DR 11.4%, HbA1c 5.7–6.0%: DR 23%, HbA1c 6.0–6.4%: DR 28.1% [ 43 ].…”
Section: Methodsmentioning
confidence: 99%